SOCIAL COMPARISON DAN BODY DISSATISFACTION PADA WANITA DEWASA AWAL - Livian Sunartio; Monique Elizabeth Sukamto; Ktut Dianovinina (Universitas Ahmad Dahlan, 2012)
AbstractMost women have a concern toward their physical appearance.Therefore, they often compare their physical appearance, especially their body shape, with other women’s body shapes which are more attractive. The purpose of this study was to examine the correlation between social comparison and body dissatisfaction among early adult women. Social comparison is the process of comparing oneself with others, whereas body dissatisfaction is the negative individual’s feelings, thoughts, and evaluation toward her body shape. Social comparison and body dissatisfaction were measured using Body Comparison Scale (BCS) and Body Shape Questionnaire (BSQ). The participants were 104 female students of Faculty of Psychology, University of Surabaya aged 18-25 years old. The result showed that social comparison was positively correlated with body dissatisfaction among early adult women (r= .636, p< .05). It means that the early adult women are more prone to experience higher bodydissatisfaction if they more often compare their body shapes with more attractive women.Keywords: body dissatisfaction, early adult women, social comparison